Intermolecular Interaction for Ternary Mixture of N-Methylmoprphline with Aromatic Hydrocarbons with Determined Densities to Measure Excess Molar Volume - Sali Nabeel Jabrou (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The determination of excess molar volume, which is dependent on the nature of liquid mixtures as well as intermolecular interactions, is the main emphasis of the presented study. For the mixture of N-methylmorpholine + o-xylene, benzene + N-methylmorpholine (NMM) + toluene+ benzene, and N-methylmorpholine + benzene+ mesitylene, as well as constituent binary mixes of benzene, N-methylmorpholine + N-methylmorpholine + N-methylmorpholine + o-xylene+ toluene, and N-methylmorpholine + mesitylene at 298.15K under atmospheric pressure, excess molar volume was computed from measured data of density over the entire range of mole fraction.